2016
DOI: 10.1111/jgh.13414
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for sustained hepatitis B e antigen seroconversion to peginterferon alfa‐2a in chronic hepatitis B

Abstract: We successfully established prediction models for PEG-IFN response in HBeAg-positive CHB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…However, NUCs and IFN-α alone or combined treatment are rare to achieve functional cure (Reijnders et al, 2010; Zoulim and Locarnini, 2012; Terrault et al, 2016; Revill et al, 2019). Extensive studies have identified host genetic genes, alanine aminotransferase (ALT) levels, HBV genotype, and HBV DNA, anti-HBc, and HBsAg levels as important predictors of treatment efficacy (Brouwer et al, 2014; Fan et al, 2016b; Zhu et al, 2016a). Accumulating evidence suggests that host genetics play an important role in the patient response to IFN-α or NUCs ( Table 3 ; Tables S1 , S5 , S6 ).…”
Section: Antiviral Efficacy Of Interferon-α or Nucleos(t)ide Analoguesmentioning
confidence: 99%
“…However, NUCs and IFN-α alone or combined treatment are rare to achieve functional cure (Reijnders et al, 2010; Zoulim and Locarnini, 2012; Terrault et al, 2016; Revill et al, 2019). Extensive studies have identified host genetic genes, alanine aminotransferase (ALT) levels, HBV genotype, and HBV DNA, anti-HBc, and HBsAg levels as important predictors of treatment efficacy (Brouwer et al, 2014; Fan et al, 2016b; Zhu et al, 2016a). Accumulating evidence suggests that host genetics play an important role in the patient response to IFN-α or NUCs ( Table 3 ; Tables S1 , S5 , S6 ).…”
Section: Antiviral Efficacy Of Interferon-α or Nucleos(t)ide Analoguesmentioning
confidence: 99%
“…Therefore, sustained HBeAg seroconversion is a satisfactory result after treatment of HBeAg-positive chronic hepatitis B, and it is associated with improved long-term prognosis[5,6]. A rapid decline in hepatitis B surface antigen (HBsAg) and HBeAg titers during treatment implies a high rate of HBeAg seroconversion, as has been documented with interferon treatment[12,13]. These features are valuable in predicting the therapeutic effects in chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…ALT, HBeAg, and HBV DNA were subgrouped according to previous studies and their ability to predict the response to treatment was evaluated. [18,19] As shown in Table 2, ALT and HBV DNA levels were not statistically different between responders and non-responders ( P > .05). Notably, the incidence of HBeAg seroconversion was significantly higher among patients with HBeAg S/CO ≤ 500 (OR = 2.60, 95% CI: 1.16–5.83, χ 2 = 5.52, P = .02, PPV = 54.76%, NPV = 68.25%) at baseline, with HBeAg S/CO ≤ 20 (OR = 3.37, 95% CI: 1.47–7.73, χ 2 = 8.53, P = .003, PPV = 58.54%, NPV = 70.49%) or a higher than 10-fold HBeAg decline (OR = 3.55, 95% CI: 1.50–8.37, χ 2 = 8.67, P = .003, PPV = 62.16%, NPV = 68.33%) at 12 weeks, or with HBeAg S/CO ≤ 15 (OR = 10.35, 95% CI: 4.09–26.20, χ 2 = 28.03, P < .001, PPV = 64.29%, NPV = 85.19%) at 24 weeks.…”
Section: Resultsmentioning
confidence: 90%